IoT Based Security System for Smart Homes - Sheikh, Anjum (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things (IoT) enables the electronic devices to be interconnected by a network. A smart home can be considered to be a residence enabled with communication networks, home appliances and sensors that can be controlled as well as remotely accessed by the home owner. The concept of smart home has developed into a form of an artificial intelligence service that can be operated by self-understanding the behaviors of the residents. This paper has tried to propose a smart home system which will help to monitor the internal environment of the home such as temperature , gas leakage and also will help the owner to take care of the plants by watering them with the help of a remote device.